Business Ethics - A Philosophical and Behavioral Approach - Conrad, Christian A. (Springer, 2018)
The question of whether or not there is a need for ethics in business is still a scientific discussion. However, in the context of the 2000 Enron crisis, the first doubts arose as to whether a business enterprise without morality could work. Since the financial crisis that began in 2007, the economy and business administrations are increasingly confronted with the demand for more social responsibility. A common feature of the crises was the immoral enrichment efforts of managers at the expense of their companies and the system, and thus society. The market economy system places the individual at the forefront of economic value creation and grants him a great freedom of development. The pursuit of self-interest is intended to ensure the greatest possible motivation for the individual, and thus a maximum result for the general public seems to work less and less. The central question to be answered in this textbook is the extent to which moral values play a role as productive forces for the economy. Our underlying method is a scientific approach. In this case, no normative approach is deliberately pursued and a morality is not demanded a priori by the economy. This morality would have to be subjectively and culturally relativized and could therefore claim no universality. Moral values in themselves, such as the dignity of man, should not be regarded as a requirement profile without logical reasoning, although they have a high target priority. Normative, moral, perhaps even emotional-related goals such as justice should be mentioned, but should not be used for argumentation when they are not productivity-enhancing. The aim is the optimal development of the productive forces in companies and national economy, i.e., the simple increase in welfare through output maximization while taking into account the welfare of all parties involved. A system of ethics founded purely on logic will be devised, one which stimulates the productive forces of the market economy. The aim is to reveal the ethics implied by the market economy, an ethics that can also claim international validity for the globalized economy. We hope to justify and promote ethics objectively and thus convincingly.